An overview of Staphylococcus epidermidis and Staphylococcus aureus with a focus on developing countries - Daniela Chessa; Giulia Ganau; Vittorio Mazzarello (Journal of Infection in Developing Countries)
Most nosocomial infections by Staphylococcus epidermidis and Staphylococcus aureus have gained considerable attention due to an increase of infections caused by these strains that have been reported in recent years throughout the world. Most notably, it is important to underline the presence of S. epidermidis and S. aureus in the human epithelia microflora and to highlight that it is impossible to eradicate them from humans. There are various virulence factors that normally sustain the infection life cycle, such as antibiotic resistance (methicillin resistance). Furthermore, it is important to evaluate the usefulness of typing the spa gene from isolated strains in order to study genotypes and geographical distributions. In the present review, different cases related to patients infected by Staphylococci and an overview of this problem worldwide are reported.